2013
DOI: 10.1017/s1041610213001634
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in elderly Korean population: a two-year longitudinal study

Abstract: Depressive symptoms were independently associated with prevalent, incident, and persistent SI, but other predictors varied according to incidence and persistence outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Interestingly, that study also showed that mental illness such as depressive disorder could only mediate the onset of ideation rather than attempts, which was consistent with our results. In another longitudinal study in elderly Koreans (Kang et al, 2014), incident suicidal ideation was related to marriage status, social support, severe pain and depression, whereas persistent suicidal ideation was related to baseline stressful life event and depression. Therefore, incident suicidality, recurrent/persistent suicidality and incident suicide attempts, although can be described as an umbrella term 'suicidal behavior', may have different etiologies or risk factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, that study also showed that mental illness such as depressive disorder could only mediate the onset of ideation rather than attempts, which was consistent with our results. In another longitudinal study in elderly Koreans (Kang et al, 2014), incident suicidal ideation was related to marriage status, social support, severe pain and depression, whereas persistent suicidal ideation was related to baseline stressful life event and depression. Therefore, incident suicidality, recurrent/persistent suicidality and incident suicide attempts, although can be described as an umbrella term 'suicidal behavior', may have different etiologies or risk factors.…”
Section: Discussionmentioning
confidence: 92%
“…First, methodological differences might have contributed to the discrepancy. For example, in the study conducted by Kang et al that had reported one-month prevalence rate of suicidal ideation to be 11.5% in elderly aged 65 years or older, the researchers did not include suicide plans, attempts, and the lifetime history of suicide attempt in their assessments of suicidality (Kang et al, 2014). In our population, the prevalence of lifetime history of suicidal attempt without current suicidality was 6.4% (95% CI ¼4.5-8.3).…”
Section: Discussionmentioning
confidence: 99%
“…The course of suicidal ideation in late-life depression is predicted by depression severity [20, 23], a previous attempt, and seriousness of suicidal intent [20]. Finally, persistent suicidal ideation is independently predicted by depressive symptoms and life stressors [24]. …”
Section: Recent Findings On Major Depression Schizophrenia and Suicmentioning
confidence: 99%
“…Research has identified many factors associated with older adult suicidal ideation and behavior. One of the most salient is psychopathology, particularly major depression . Research in the United States, South Korean, Brazilian, and Australian older adults suggests that psychological distress generally and major depression specifically account for the most variance in models examining suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%